2021
DOI: 10.3389/fpsyg.2021.634910
|View full text |Cite
|
Sign up to set email alerts
|

Love Forgiveness and Subjective Well-Being in Chinese College Students: The Mediating Role of Interpersonal Relationships

Abstract: Love forgiveness is categorized as forgiveness in a specific relationship, which is the tendency of individuals to forgive the objects of their interpersonal relationships. We investigated 831 undergraduate students in China with a love forgiveness questionnaire, a subjective well-being questionnaire and an interpersonal relationship comprehensive diagnostic, including demographic variables. Students of different genders and grades showed significant differences across the three questionnaires. There were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…College students who are good at interpersonal relations and aggressive are more likely to fall in love. Studies have shown that the better the interpersonal relationship, the higher the love forgiveness ability, so the longer the love will be [21]. It is verified by scientists that the physical activity is beneficial for not only physical health, but also mental health of college students [22].…”
Section: Resultsmentioning
confidence: 99%
“…College students who are good at interpersonal relations and aggressive are more likely to fall in love. Studies have shown that the better the interpersonal relationship, the higher the love forgiveness ability, so the longer the love will be [21]. It is verified by scientists that the physical activity is beneficial for not only physical health, but also mental health of college students [22].…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, gender is a demographic factor that has been researched in correlation to AQ. According to some studies, females tend to have higher levels of AQ than males (Zhang et al, 2020), whereas other studies have identified no substantial gender differences in AQ (Qin et al, 2019;Stoltzfus & Nisbett, 2020). Gender differences in AQ could be affected by societal norms and gender roles.…”
Section: Comparison Of Adversity Quotient Between a Male And Female E...mentioning
confidence: 99%
“…These social‐psychological factors are also called “latent variables” or “latent factors,” because they cannot be fully measured by a single observed variable, but should instead be assessed through a number of questionnaires from different perspectives. For example, childhood trauma was measured by tests reflecting emotional abuse (EA), physical abuse (PA), and physical neglect (PN), 4 interpersonal relationship was evaluated through a series of tests about conversational ability (CA), communicative competence (CC), manner of dealing with people (MDP), and opposite‐sex communication (OSC), 5 whereas family burden of disease was characterized by family financial burden (FFB), daily family activities (DFA), family entertainment (FE), and family relations (FR) 6 . Multiple surrogates of a latent factor are often highly correlated because they share certain similarity elicited by this latent factor.…”
Section: Introductionmentioning
confidence: 99%